2017
DOI: 10.14198/jhse.2017.122.15
|View full text |Cite
|
Sign up to set email alerts
|

Maximal heart rate differs between laboratory and field conditions among female athletes

Abstract: The purpose of this study was to determine if maximal heart rate (MHR) varies between laboratory testing, field testing, training, competitive matches and an age predicted MHR equation among female collegiate soccer players. 21 female NCAA Division 1 soccer players had MHR determined during a maximal treadmill test (MHRGXT), a 20-meter shuttle run test (MHRFIELD), 4 weeks of early season training (MHRTRAIN), 5 competitive matches (MHRMATCH), and an age prediction equation (MHRPRED). Participants were excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…In another study, mode of exercise, fitness level, continent, and age were predictors of HR max (Londeree and Moeschberger, 1982 ). Moreover, caution is needed to generalize the values obtained in the GXT in the laboratory to other settings, e.g., field testing, training and competition, as the latter might induce higher values (Coutinho et al, 2017 ). Nevertheless, strength of the present study was its novelty as it was the first to be contacted on recreational marathon runners.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, mode of exercise, fitness level, continent, and age were predictors of HR max (Londeree and Moeschberger, 1982 ). Moreover, caution is needed to generalize the values obtained in the GXT in the laboratory to other settings, e.g., field testing, training and competition, as the latter might induce higher values (Coutinho et al, 2017 ). Nevertheless, strength of the present study was its novelty as it was the first to be contacted on recreational marathon runners.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study have several implications. First, numerous studies have demonstrated that neither age-predicated maximum HR calculations nor maximum HR assessed by laboratory measurements of VO 2 max accurately predicts maximum HR performance during competition [15][16][17]. Moreover, the exhaustive review by Robergs and Landwehr [18] documents the shortcomings of all published approaches to estimating maximum HR in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Dependiendo de la prueba y del laboratorio utilizado, hay diferencias entre test de campo en fondistas competiendo (206 ± 4 latidos•min -1 ) o entrenando (207 ± 5.0 latidos•min - 1) frente a los test de laboratorio (194 ± 2 latidos•min -1 ) (Boudet et al, 2002;Jeukendrup y Diemen, 1998;Kunduracioglu, Guner, Ulkar y Erdogan, 2007;Lambert, Mbambo y Gibson, 1998;Semin et al, 2008). Incluso se ha reportado en otros deportes (Coutinho, Watson, Brickson, y Sanfilippo, 2017). Se ha observado, durante test de campo, que la concentración sanguínea de lactato, medida a una FC dada, es mayor que la medida durante un test de laboratorio (Vergès, Flore y Favre-Juvin, 2003).…”
Section: Umbral Anaeróbico Aspectos Didácticosunclassified